Why is my community reacting like this? Understanding reactions in open-source communities - Melgarejo, Jorge Luís; Fontão, Awdren de Lima; Borges, Hudson Silva (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3578, 2024)
In 2016, GitHub introduced the “Reactions” feature to facilitate the expression of sentiments and reduce noise in communications on its platform. Recent studies indicated that developers has been adopting the feature and was observed a reduction of noise on conversations inside the platform. However, the patterns of usage and profiles of users expressing these reactions in inside their communities remain underexplored. Identifying these patterns may help maintainers to better understand members’ behaviors in their communities, and researchers to build supporting tools focused on users’ reactions. This paper presents an initial study to (i) understand these interactions on open-source software communities, (ii) identify types of resources that receive the most reactions, (iii) analyzing seasonal factors influencing usage, and (iv) correlating the provided reactions with the roles of developers within the community. Preliminary results indicate that users primarily react to comments in Issues, with notable periods of heightened activity. Additionally, significant differences were observed between the reactions of maintainers and other members of the community.